Numerical and experimental study of mechanical properties and hydrostatic behavior of PVC-O material for drinking water pipes - Dilshad Azad Mohammed; Mohammedtaher M. Saeed Mulapeer (Zanco Journal of Pure and Applied Sciences, 2021)
This study investigates the mechanical properties for oriented polyvinyl chloride PVC-O material from three different directions of stress application. A PVC-O 500 pipe material has been studied in terms of mechanical properties in three different directions (0o, 45o, 90o). Tensile strength at yield and percent elongation at fracture has been determined in all three directions. Two types of end caps (A and B) have been used to evaluate the pipe's hydrostatic strength. Results showed that molecular orientation has a significant impact on the pipe strength and ductility in different directions. Increasing the molecular orientation in the direction of the hoop (90o direction), the strength increased to 91 MPa compared with 0o and 45o direction, which were 49 MPa and 61 MPa, respectively. Results showed that the percentage of elongations was 200%, 76 %, and 61% for 0o, 45o, and 90o directions, respectively. The burst pressure for type A and B end caps was 6.22 MPa. Finite element analysis by SolidWorks 2018 simulation has been employed; the FEA has showed a good agreement with experimental results with a maximum difference of 5.16%. The FE results also showed that end caps affect stress distribution around the pipe during the hydrostatic test specially when using type B end caps. It's also concluded that both types of end caps cause stress concentration near the edges of the caps.